Wings : Final Season The final season - Daly, Tim, 1956-; Weber, Steven, 1961 March 4-; Bernard, Crystal; Schramm, David; Shalhoub, Tony, 1953-; Schull, Rebecca; Yasbeck, Amy, 1962-; CBS Studios Inc.; CBS Paramount Network Television (Firm); Paramount Pictures Corporation; Grub Street Productions; Paramount Home Entertainment (Firm); et al. (Hollywood, Calif. : Paramount Home Entertainment, 2009)
Brothers Brian and Joe Hackett attempt to run a Nantucket-based airline, Sandpiper Air, while surrounded by their wacky friends and co-workers at Tom Nevers Field.
Title from container.
Originally broadcast on television during the 1996-1997 season.
Contains all 23 episodes from the final season.
Tim Daly, Steven Weber, Crystal Bernard, David Schramm, Tony Shalhoub, Rebecca Schull, Amy Yasbeck.
DVD; region 1; NTSC; full screen (1.33:1) presentation; Dolby Digital stereo.
Closed-captioned.
Keywords: Aeronautics, Commercial -- Chartering -- Massachusetts -- Nantucket Island -- Drama; Brothers -- Massachusetts -- Nantucket Island -- Drama; Fiction television programs; Video recordings for the hearing impaired; Comedy television programs